U.S. Department of Health Adverse Event Reporting Policies for Nursing Homes. Issue 3 (21st November 2011) - Wagner, Laura M.; Castle, Nicholas G.; Reid, Kathleen C.; Stone, Robyn
Abstract The objectives of this study were to describe state policies for the frequency of adverse event reporting and follow‐up that occurs in U.S. nursing homes, and to identify the health information technology used to facilitate these processes. The study was conducted using a mailed survey to the Departments of Health (DOH) in all 50 states, specifically the department that is responsible for the oversight and regulation of nursing home care. Thirty‐two state DOH representatives participated. The primary variables examined were (1) which incidents were most commonly reported to state DOH and (2) whether or not they were followed up with a surveyor visit to the nursing home. There was wide variation in incident reporting processes across all states and lack of a standardized process. Abuse is the only adverse event that almost always is required to be reported to the state DOH and has the highest incidence of follow‐up with a surveyor visit. Improving and standardizing adverse event reporting systems is a necessary strategy to enhance patient safety in nursing homes. This study provides an important step by increasing our knowledge base of the current state of adverse event reporting policies and processes at the state level.